Little Miss Greedy - Hargreaves, Roger (World international Limited, 1981)
Little Miss Greedy is the 13th book in the Little Miss series. Little Miss Greedy has the same appetite as her cousin and has a really large breakfast.
Keywords: Juvenile Fiction-Book